Creative Leveraging in Contingent Faculty Organizing. Issue 3 (September 2015) - Rhoades, Gary; Newfield, Marcia; Berry, Joe; Kroik, Polina
<x xml:space="preserve">Abstract</x> Contingent faculty members are marginally situated at the bottom of a highly stratified academic workforce in the academy. Yet they are central to and at the lead of the academic labor movement. What contingent faculty members, groups, and unions lack in formal positions of power is more than made up for by their creative leveraging of the not inconsiderable resources and positions of influence available to this precarious professoriate (or professorial precariate). In this article, I offer observations of developments in contingent activism from the standpoint of a tenured ally and privileged participant in the struggle, as well as from the position of a sociologist studying and seeking to provide supportive suggestions to groups, unions, and to activists whose livelihoods are daily on the line.